PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIME TOKEN DALAM MENINGKATKAN HASIL BELAJAR SISWA - Anugrahwati, Yulia; Salim, Izhar; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis is entitled "the influence of the use of Time Token Cooperative learning models on Integrated Social Studies subjects in improving the learning outcomes of VIII grade students in SMP N 11 Pontianak". The problem in this study is whether the influence of the use of Time Token cooperative learning models on Integrated Social Studies subjects in improving the learning outcomes of VIII grade students in Pontianak N 11 Middle School? This study aims to determine the effect of the use of Time Token cooperative learning models on Integrated Social Studies subjects in improving the learning outcomes of VIII grade students in 11 SMP N Pontianak. The research method used is the experimental method with the form of nonequivalent control group design. The population amounted to 231 students, the selection of samples using purposive sampling technique, data collection tools in the form of tests namely pre-test and post-test. in the results of the study, the mean value of the post-test control class was 71.29 and the average results of the post-test experimental class 76. The results of the t-test revealed that the value of Sig. (2-tailed) at the pre-test value of 0.041 <0.05, and at the post-test value of 0.038 <0.05, thus it is known that Ho is rejected and Ha is accepted. It was concluded that there were differences in student learning outcomes using the Time Token Cooperative learning model. with an acquired size of 2.08 which is relatively high.. Keywords: Influence, Cooperative Time Token, Learning Outcomes.